2018
DOI: 10.21037/acs.2018.01.07
|View full text |Cite
|
Sign up to set email alerts
|

Current state of pediatric cardiac transplantation

Abstract: Pediatric heart transplantation is standard of care for children with end-stage heart failure. The diverse age range, diagnoses, and practice variations continue to challenge the development of evidence-based practices and new technologies. Outcomes in the most recent era are excellent, especially with the more widespread use of ventricular assist devices (VADs). Waitlist mortality remains high and knowledge of risk factors for death while waiting and following transplantation contributes to decision-making ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
95
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(99 citation statements)
references
References 74 publications
2
95
0
2
Order By: Relevance
“…The International Registry of Paediatric Heart and Lung Transplantation (ISHLT) is the largest registry to collect data regarding cardiac transplantation in children. 1 Figures stated in this article will be from this database unless stated otherwise. The number of cardiac transplants in children has increased annually from 414 in 2000 to 684 in 2015.…”
Section: International Cardiac Transplant Caseloadmentioning
confidence: 99%
See 3 more Smart Citations
“…The International Registry of Paediatric Heart and Lung Transplantation (ISHLT) is the largest registry to collect data regarding cardiac transplantation in children. 1 Figures stated in this article will be from this database unless stated otherwise. The number of cardiac transplants in children has increased annually from 414 in 2000 to 684 in 2015.…”
Section: International Cardiac Transplant Caseloadmentioning
confidence: 99%
“…Multiple studies have demonstrated equivalent outcomes from ABO-compatible and -incompatible transplants in small children. 1 Successful transplantation of ABO-incompatible organs requires three factors: specialist techniques to reduce the isohaemagglutinins titres before reperfusion of the new organ place; effective immunosuppression; and early treatment of antibody-mediated rejection (AMR).…”
Section: Abo Compatibilitymentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, the survival outcomes following subarachnoid haemorrhage and severe neurotrauma have improved with reducing mortality after head injury . The number of heart transplants has remained fairly constant, with waiting list mortality for paediatric patients awaiting heart transplantation at 1 year remains at 17% and as high as 30% in the infant group . This unacceptable waiting list mortality led us to perform transplant using a DCD donor, which currently account for <0.05% of paediatric heart transplants …”
Section: Introductionmentioning
confidence: 99%